2011
DOI: 10.1590/s0102-36162011000500008
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia a curto prazo do laser de baixa intensidade em pacientes com osteoartrite do joelho: ensaio clínico aleatório, placebo-controlado e duplo-cego

Abstract: Objective: This study was designed to evaluate the short-term efficacy of low-level laser therapy (LLLT) for improving pain and function in patients with knee osteoarthritis. Methods: Forty-seven patients with knee osteoarthritis (79 knees), of both genders, participated in this randomized controlled double-blind clinical trial. They were randomly allocated to two groups: laser group with 25 patients (41 knees) and placebo group with 22 patients (38 knees). LLLT was performed three times a week, totaling nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
(22 reference statements)
2
1
0
8
Order By: Relevance
“…The results of this study are similar to the result of Fukuda et al who found a significant improvement in pain and function in the laser group (energy of 3.0 J per point) compared with placebo in all the assessments applied to the groups [48]. Similar results were found in clinical trials of Rayegani et al [49] and Hegedus et al [50].…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study are similar to the result of Fukuda et al who found a significant improvement in pain and function in the laser group (energy of 3.0 J per point) compared with placebo in all the assessments applied to the groups [48]. Similar results were found in clinical trials of Rayegani et al [49] and Hegedus et al [50].…”
Section: Discussionsupporting
confidence: 90%
“…(6) Estudos foram conclusivos que o laser de baixa intensidade e o TENS são eficazes na melhora da dor em pacientes com osteoartrose e na melhora da funcionalidade desses pacientes, e mais, esses recursos físicos, ao contrário dos fármacos analgésicos e anti-inflamatórios, não apresentam os indesejáveis efeitos adversos. (7,8) A incontinência urinária (IU) não é problema exclusivamente do processo de envelhecimento, porém com o avanço da idade, se agrava consideravelmente, seja por comprometimentos de outras patologias ou por efeito de medicamentos utilizados para tratar tais distúrbios ou disfunções orgânicas. (9) Tendo em vista a variedade de opções disponí-veis para utilização pelo fisioterapeuta no tratamento de diferentes acometimentos em idosos, este estudo tem como objetivo apresentar quais são os principais recursos terapêuticos aplicados na reabilitação do idoso de acordo com as disfunções e patologias mais comuns.…”
Section: Principais Achadosunclassified
“…Morgan et al (2011), relatam ser possível a diminuição de dor articular em portadores de osteoartrite de joelho com o uso do TENS, (8) sendo também proveitoso o tratamento com laser sobre os mesmos casos, com sinais de melhora a curto prazo. (7) A eletroestimulação neuromuscular pode ser proveitosa no tratamento de patologias degenerativas, de joelho e coluna vertebral. A ação seletiva da eletroestimulação sobre os músculos multífidos lombares, após a realização de exercícios de estabilização, pode atuar na recuperação do seu tônus e trofismo, promovendo uma melhor estabilização da coluna vertebral, resultando em menos dor pelo paciente.…”
Section: Metodologia Mecanismo De Buscaunclassified
“…Water physical and physiological properties enable exercises hardly performed on the ground and which, associated to better movement amplitude and high water temperature, increase joint mobility, muscle control and resistance, relieving pain and accelerating functional recovery process 27 . With regard to electrotherapy, a randomized, placebo-controlled and double-blind clinical trial has shown that low intensity laser therapy was effective, in the short term, to improve pain and function of knee OA patients 28 . A randomized, prospective and blind study 29 has compared physiotherapy protocols involving kinesiotherapy, cryotherapy and short waves in knee OA patients and has observed that the best protocol was that involving ice application and kinesiotherapy for analgesia; however there has been no amplitude, flexibility and strength gain associated to cryotherapy.…”
Section: Osteoarthritismentioning
confidence: 99%